The Relationship Mental Health and Work Productivity among Male Police and Female Police in Yogyakarta - Nana Oktaviana Abrilia; Farida Harahap (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Police work is quite high-pressure, but police officers must remain productive in any situation. This research examined the relationship between mental health and work productivity among male and female police officers at the Yogyakarta City Police Department. The method used for technique for sampling was proportional sampling. The subjects of this research involved 250 male and female police officers at the Yogyakarta City Police Department. The data collection technique used a questionnaire with a Likert scale to measure mental health and police work productivity. The analysis technique employed in this study was Partial Least Squares (PLS), utilising the SmartPLS 3.0 software. Hypothesis testing used Bootstrap. The value taken was the t statistic value and/or p value. The limits were >1.96 (t statistic) and <0.05 (o value). From the test results, it was found that (1) Male and female police officers consider mental health parameters in supporting their productivity, (2) There are significant differences in mental health variables for male and female police officers, (3) Mental health of male police officers and men higher or stable when compared to female police officers. In conclusion, mental health plays an essential role in the productivity of police work, and improving mental health will positively impact the effectiveness of law enforcement.